Penerapan MSMP (Mooring System Management Plan) untuk Keselamatan Kapal Saat Sandar di Jetty - Hentri Widodo, B.L; Tri Wahyuni, Eni; Satrio, Renaldy (PPPM Polimarin, 2024)
This research aims to find out and understand the implementation of the mooring system, ship safety and crew safety, and how the ship crew prepares for the docking process at the jetty. Some of the consequences that arise if the mooring system management plan is not implemented are that it can result in safety threats, both the safety of the ship and the safety of the crew themselves. Among them are ropes breaking when the ship is at the jetty, damage that occurs on board the ship and even injuries to the crew can also result in death, as was the case with the MV Mutiara Persada 2 ship which was docked at the Merak pier at that time. The role of the ship's crew is in implementing a periodic maintenance system for all ropes on board the ship when necessary in accordance with the ship maintenance Safety Management System. Mooring arrangements on ships must be strictly implemented, especially for tanker types, and should refer to the Mooring Equipment Guideline issued by OCIMF (Oil Companies International Marine Forum). Likewise, the lay out of the rope when the ship is berthed at the jetty must also be adjusted to the DWT (Dead Weight Tonnage) of the ship itself to avoid the rope breaking due to supporting the weight of the ship which is not in accordance with the weight of the ship. The writing method in this research is literature study and documentation, as well as descriptive data in the form of writing from several sources. The results of the discussion can be concluded that good rope maintenance management can minimize the impact of rope breaking when the ship is docked at the dock, as well as the implementation of a good mooring system management plan can also avoid the negative impacts that arise or the ship's rope breaking when the ship is docked at the jetty. By adjusting the appropriate rope layout and mooring arrangement in accordance with the regulations determined by OCIMF. So the safety of the ship and crew is very important when sailing or when the ship is at the jetty when loading and unloading